Rapid determinations of moisture content in crude palm oil by fourier transform infrared spectroscopy - Che Man, Yakoob; Mirghani, Mohamed Elwathig Saeed (Springer Berlin, 2000)
A simple, rapid, and direct Fourier transform infrared (FTIR) spectroscopic method was developed for the determination of moisture content of crude palm oil (CPO). The calibration set was prepared by adding double-distilled water to dried CPO in ratios (w/w) between 0 and 13% moisture. A partial least squares (PLS) regression technique was employed to construct a calibration model followed by cross-validation step. The accuracy of this method was comparable to the accuracy of the American Oil Chemists’ Society’s vacuum oven method, which is used for determination of moisture and volatile matter, with mean difference (MDa) of 0.0105, a coefficient of determination (R2) and a standard error of calibration (SEC) of 0.9781 and 0.91, respectively. It is also comparable to the accuracy of the International Union of Pure and Applied Chemistry’s distillation method with MDa, R2, and SEC of 0.0695, 0.9701, and 0.65, respectively. The study showed that midband FTIR spectroscopy combined with the PLS regression calibration technique is rapid and accurate for determination of moisture content of CPO samples with a total analysis time of less than 2 min and less than 2 mL of sample.